Various Words and Their Implementation in Indonesian Sentences - Ifan Zamborano; Didik Himmawan (El-Ma'wa: Journal of Arabic, Translation and Linguistic, 2025)
Words are the smallest forms or units in language that contain certain concepts or ideas. The most important element in language. Without words there might be no language, because words are the embodiment of language. This article discusses various types of words and their implementation in Indonesian sentences. The method used in this paper is a qualitative method with a library study approach from relevant sources through books and articles. Conclusions are conveyed narratively by mentioning and implementing the words in example sentences. The conclusion of this article is that words are a group of words in a language unit based on the categories of form, function and meaning in the grammatical system. To compose good and correct sentences based on standard sentence patterns, language users must first know the types and functions of word classes so that errors do not occur.